2020
DOI: 10.1038/s41598-020-75359-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial inducible expression of plant cell wall-binding protein YesO through conflict between Glycine max and saprophytic Bacillus subtilis

Abstract: Saprophytic bacteria and plants compete for limited nutrient sources. Bacillus subtilis grows well on steamed soybeans Glycine max to produce the fermented food, natto. Here we focus on bacterial responses in conflict between B. subtilis and G. max. B. subtilis cells maintained high growth rates specifically on non-germinating, dead soybean seeds. On the other hand, viable soybean seeds with germinating capability attenuated the initial growth of B. subtilis. Thus, B. subtilis cells may trigger saprophytic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In particular, alphagalactosidase (B2R_16136) and arabinose import (B2R_29105) had the highest LOD and smallest overlapping confidence intervals with chromosomes 6 and 11 (Figure 7). Indeed, many SNPs in genes involved in the degradation of xylan 58 , one of the most dominant non-cellulosic polysaccharides in plant cell-walls 59 , as well as carbohydrate and protein metabolism were linked to chromosomes 6 and 11, including xyloglucanase Xgh74A (B2R_10589), alpha-xylosidase (B2R_23763), endo-1,4-beta-xylanase (B2R_20609), extracellular exo-alpha-Larabinofuranosidase (B2R_20608), multiple protease HtpX (B2R_19218), cutinase (B2R_19356), and putative ABC transporter substrate-binding protein YesO (B2R_09821) which has been implicated in the transport of plant cell wall pectin-derived oligosaccharides 60 . A Streptomyces SNP in acetolactate synthase (B2R_28001) was linked to chromosome 6 where a plant acetolactate synthase was located.…”
Section: Genomic Structure In Cellvibrio and Streptomyces Provides Insights Into Adaptations For Differential Recruitmentmentioning
confidence: 99%
“…In particular, alphagalactosidase (B2R_16136) and arabinose import (B2R_29105) had the highest LOD and smallest overlapping confidence intervals with chromosomes 6 and 11 (Figure 7). Indeed, many SNPs in genes involved in the degradation of xylan 58 , one of the most dominant non-cellulosic polysaccharides in plant cell-walls 59 , as well as carbohydrate and protein metabolism were linked to chromosomes 6 and 11, including xyloglucanase Xgh74A (B2R_10589), alpha-xylosidase (B2R_23763), endo-1,4-beta-xylanase (B2R_20609), extracellular exo-alpha-Larabinofuranosidase (B2R_20608), multiple protease HtpX (B2R_19218), cutinase (B2R_19356), and putative ABC transporter substrate-binding protein YesO (B2R_09821) which has been implicated in the transport of plant cell wall pectin-derived oligosaccharides 60 . A Streptomyces SNP in acetolactate synthase (B2R_28001) was linked to chromosome 6 where a plant acetolactate synthase was located.…”
Section: Genomic Structure In Cellvibrio and Streptomyces Provides Insights Into Adaptations For Differential Recruitmentmentioning
confidence: 99%
“…In 2020, we found that Bacillus cells can form a “hole”-like structure in their cell surface 115 ) during growth on solid media. Briefly, when the cells of B. subtilis 168 were grown in a nutrient medium solidified with agar, the cells shrank at the end of growth ( Fig.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A1, 120 123 ) PVA-degrading enzymes in Sphingopyxis sp. 113P3, 112 114 ) and plant cell wall (pectin)-degrading enzymes in B. subtilis , 115 , 124 − 132 ) respectively. In other words, applied studies led to the discovery of novel basic biological phenomena, which will expand and develop new areas of microbiology and bioscience.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Among pectin-degrading enzymes, polygalacturonase is genetically encoded and expressed by grape-skin resident species and by S. cerevisiae 42,43 . Recently, we revealed the importance of pectin as an initial target for the saprophytic bacterium Bacillus subtilis to recognize the surface of dead soybeans 44 , whereas it is unlikely that pectin degradation by non-Saccharomyces microorganisms specifically accelerated alcoholic fermentation of intact grapes. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%